Investigation of Heat Transfer on a Rotating Latent Heat Energy Storage. (May 2017) - Kurnia, Jundika Candra; Sasmito, Agus Pulung; Ping, See Itt
Abstract: During charging and discharging process of latent heat energy storage, higher energy transfer is commonly observed at higher area. Therefore, by slowly rotating the energy storage, a more uniform and higher heat transfer is expected. The objective of this study is to numerically investigate the heat transfer performance of rotating latent heat energy storage. A three-dimensional computational model representing latent heat energy storage is developed and validated against experimental data. The model is then utilize to investigate the conjugate heat transfer between heat transfer fluid (HTF) and phase change materials (PCM) as energy storage medium. The heat transfer performance between steady and rotating energy storage is compared. The results indicate that rotating latent heat energy storage offers superior heat transfer performance as compared to its steady counterpart. In addition, it was found that slower rotational speed results in higher heat transfer as compared to higher rotational speed.